Moral integration influences English as a Foreign Language (EFL) oral English learning: Evidence from textbook analysis and learner feedback - Yang, Xixi; Nie, Qi (PLOS ONE, 2026)
The research is motivated by the strategic integration of moral and value education into China’s college English curriculum and the critical role of textbooks as value carriers in EFL education. Despite growing attention to value integration in EFL materials, empirical studies on moral and value representation in oral English textbooks remain sparse, and learners’ perspectives on value acquisition through oral instruction are underexplored—this study aims to address these gaps. The study employed a mixed-methods approach: the researcher systematically analyzed 318 pages of New Inside Out Book 1 and Book 2 (first-year college EFL oral English textbooks), screening all module types including vocabulary, grammar, dialogue, listening, reading, writing, and exercise for value-related content, which was then coded and recorded in Excel. Frequency statistics show the sample textbooks include 273 value-laden verbal text samples, with a Chi-Square Test revealing statistically significant differences in dimension emphasis between the two volumes. Within Martin and White’s (2005) Language Appraisal Theory, qualitative textual analysis identifies the value significance of linguistic resources as a prominent feature across module types. Additionally, to gather learner feedback on the effectiveness of value education in the oral English course, an online questionnaire survey (via Wen Juan Xing platform) was administered to learners who used the selected EFL oral English textbooks for a whole academic year. The survey showed that values-based EFL instruction positively impacted morality and personal growth.